A Christmas garland [large type] : a novel - Perry, Anne (Perry, Anne. Christmas novels., 2012)
The year is 1857, soon after the tragic Siege of Cawnpore. In the British garrison, a guard is killed and an Indian prisoner escapes. Cries for revenge ring out. Despite no evidence against him, British orderly John Tallis is arrested simply because he was unaccounted for at the time. Young lieutenant Victor Narraway is chosen to defend Tallis, and his superiors merely want a show trial. But a stubborn faith in justice inspires Narraway to search for the truth.